Battery Management Optimization Considers The State Of Charge Using The Coulomb Counting Method - Triwijaya, Santi; Pradipta, Andri (Geuthèë Institute, 2023)
The Battery Management System (BMS) is important because more and more electronic devices and vehicles use batteries as a power source. Without BMS, battery charging can become unstable, resulting in overcharging and reducing battery life. Therefore, BMS is becoming increasingly important as part of the development of safer and more efficient technologies, resulting in more reliable and safer electronic devices and vehicles. The Coulomb Counting method is used to determine the state of charge of the battery at the beginning and end of charging. The coulomb counting method is very accurate for determining the state of charge because it calculates the incoming and outgoing electric charge from the read current value. The voltage from source to load uses a buck converter to step down the voltage from 27.3V source to 25.5V load voltage. The Coulomb Counting (CC) method is used to estimate the SOC of the battery being monitored. The CC method is accurate for estimating the SOC value during charging and discharging but cannot determine the initial SOC value. The results of the current test have an accuracy of 96.03% and the voltage test has an accuracy of 99.22%.